Allogeneic hematopoietic stem cell transplantation from unrelated donors is associated with higher infection rates in children with acute lymphoblastic leukemia—A prospective international multicenter trial on behalf of the BFM‐SG and the EBMT‐PDWP. Issue 8 (29th May 2019) - Pichler, Herbert; Lawitschka, Anita; Glogova, Evgenia; Willasch, Andre M.; von Luettichau, Irene; Lehrnbecher, Thomas; Matthes‐Martin, Susanne; Lang, Peter; Bader, Peter; Sykora, Karl W.; Schrum, Johanna; Kremens, Bernhard; et al.
Abstract: Severe infections (SI) significantly impact on non‐relapse mortality after hematopoietic stem cell transplantation (HSCT). We assessed 432 children and adolescents with acute lymphoblastic leukemia (ALL) after total body irradiation based myeloablative HSCT within the multicenter ALL‐BFM‐SCT 2003 trial for SI grade 3 or higher according to common terminology criteria for adverse events. A total 172 patients experienced at least one SI. Transplantation from matched unrelated donors (MUD) was associated with any type of SI in the pre‐engraftment period (hazard ratio [HR]: 2.57; P < .001), and with any SI between day +30 and + 100 (HR: 2.91; P = .011). Bacterial (HR: 2.24; P = .041) and fungal infections (HR: 4.06; P = .057) occurred more often in the pre‐engraftment phase and viral infections more often before day +30 (HR: 2.66; P = .007) or between day +30 and + 100 (HR: 3.89; P = .002) after HSCT from MUD as compared to matched sibling donors. Chronic GvHD was an independent risk factor for any type of SI after day +100 (HR: 2.57; P < .002). We conclude that allogeneic HSCT from MUD in children and adolescents with pediatric ALL is associated with higher infection rates, which seems attributable to an intensified GvHD prophylaxis including serotherapy and methotrexate.